Pitanguy Ligamentous Flap: A New Method to Prevent Supratip Deformity in Rhinoplasty. Issue 3 (May 2020) - Ercin, Burak Sercan; Bicer, Ahmet; Bilkay, Ufuk
Abstract : Background: A supratip deformity (SD) is an iatrogenic convexity that occurs in the cephalic region of the nasal tip. SD is still a major problem after rhinoplasty surgery. Objectives: With the method we have described a ligamentous flap was used to create a supratip transition, with adjustable sharpness, while the refinements of the tip rotation and definition were ensured. The aim of the study is to present the results of this technique, which, to the best of our knowledge, has been described here for the first time. Methods: Our ligamentous flap technique was applied to 24 patients between August 2017 and March 2018. All of the patients were evaluated in terms of the formation of an SD, a hanging columella, tip projection, and the loss of rotation at the postoperative followups. The photos of patients were evaluated by another independent plastic surgeon and patients themselves at 3 months after the surgery. Results: There were no early or late complications, such as an infection, excessive bleeding, or prolonged edema. Moreover, SDs, hanging columellas, tip projections, and rotational losses, which would require revisions, were not detected in any of the patients. Postoperative scores given by the patients and surgeons were significantly higher than the preoperative values ( P < 0.05). Only 2 patients required minor revisions due to dorsal irregularities in the upper 1/3 of the nasal segment. Conclusion: The early results of this Pitanguy composite flap technique, which can be easily applied in every case with thin or thick skin in an open rhinoplasty, are promising. However, there is a need for an evaluation of the long-term results, as well as the advantages and disadvantages in a larger case series. Level of Evidence: Level IV. Abstract : Supplemental Digital Content is available in the text